The Effect of Expanding and Granulation Used During Feed Production on Poultry and Swinw Compound Feed - Kiss, Brigitta; Erdélyi, Márta; Such, Nikoletta; Tewelde, Kesete Goitom; Dublecz, Károly (GEORGIKON FOR AGRICULTURE, 2024)
During feed production, the feed raw materials that make up the feed mixture undergo various thermal and mechanical treatments, however, we do not consider these effects as influencing factors when formulating. In our experiment, we examined 19 compound feed with respect to insoluble (IDF), soluble (SDFP), and neutral detergent fiber (NDF). In the plant, the samples were taken after the mixer, after the expander, and after the press, so a total of 57 mixed feed samples were examined. We determined the amount of crude fiber, the IDF and SDFP content using an analytical method. We examined the fiber fractions using the Van Soest method. Depending on the production technology, significant differences were observed regarding IDF, SDFP, and raw fiber. The IDF content of all feed mixtures was 13.24% in the  pellets, which significantly decreased (P
Keywords: water-soluble fibers; water-insoluble fibers; feed production; expanding; granulation